Pengendalian Kualitas Produk Roti Menggunakan Six Sigma DMAIC - Silvia Firda Utami; Koko Hermanto; Muhammad Basrik Saputra (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Quality control is an important function in a business. Companies that prioritize product quality control have significant advantages in terms of stability, safety, and business sustainability. UD. Roti Jase is one of the food industries facing problems related to a high number of defective products, which has resulted in decreased revenue. The purpose of this study is to identify the causes of defects in the bread production process to produce high-quality bread. The Six Sigma DMAIC method was used to analyze these problems. Based on the analysis results, the most common defect was burnt bread, with a percentage of 31.80%. The DPMO value was 159,701, indicating that the company operates at a 3.2 Sigma level. The factors that most significantly influenced the defects were machine and human factors, namely the absence of a digital temperature control device and workers’ lack of attention during the production process. Quality improvement efforts at UD. Roti Jase to minimize defects include providing a digital temperature device, conducting direct supervision during the production process, and recruiting additional workers.